The Free Fatty Acid Reduction Using Cacao (Theobroma cacao L) Bean Husk Charcoal In Used Cooking Oil - Dafit Ari Prasetyo; Dicky Adi Tyagita; Cahyaning Nur Karimah; Alex Taufiqurrohman Zain; Umi Sholikah (Jurnal Teknik Terapan, 2026)
Used cooking oil if not well-maintained will give some problems to drainage system or surface water. Used cooking oil has the potential to be processed into energy. However, the high free fatty acid (FFA) as a result of the use of cooking oil makes the process into energy more difficult. Because the high free fatty acid content will cause the saponification reakction in making used cooking oil into energy. Cocoa bean husk charcoal (Theobroma cacao L) has a K2CO3 content that similar to its commercial product, and also contains some traces of silicates and sulfates so that it can increase the efficiency of free fatty acids removal in used cooking oil. In this study, tests were carried out to reduce FFA levels in used cooking oil using charcoal from cocoa bean husks activated with 10M of hydrochloric acid, varying the concentrations of 5, 7.5, and 10%-m/v, as well as the temperature treatment during the process of mixing used cooking oil with activated charcoal adsorbent, which was 75, 100, and 150°C. The best FFA reduction results were found in the C2T2 reactor which reached 75% of FFA removal, where the best concentration of cocoa bean husk charcoal as an adsorbent were 7.5%m/v and the temperature of the mixing process was 100°C which can remove FFA content from 2.72 to 0.64